A gynocritical study of The Company of Wolves by Angela Carter - Nouri, Azadeh,Aziz Mohammadi, Fatemeh (online, 2015)
Abstract: In 1979, Carter published one of her mast renowned collections of short fiction, The Bloody Chamber. The majority of Angela Carter's work revolve around a specific type of feminism, radical libertarian feminism and her critique of the patriarchal role that have been placed on women. which she promotes feminist due to her style, referred to as
10.18052/www.scipress.com/ILSHS.48.100
Keywords: (thesoz)Literatur; (thesoz)Erzählung; (thesoz)Feminismus; (thesoz)Emanzipation; (thesoz)Patriarchat; (thesoz)Liebe; (thesoz)Pornographie; Carter; A.